2021
DOI: 10.1097/jcn.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Self-efficacy, Perceived Benefits, and Barriers to Exercise Among Patients Following Acute Myocardial Infarction

Abstract: BackgroundIncreasing patient adherence to regular exercise post acute myocardial infarction (AMI) is a major goal after hospitalization. It is therefore essential to identify perceived benefits and barriers to exercise and its association with exercise self-efficacy among patients post AMI.AimsThe purpose of this study was to identify the perceived benefits and barriers to exercise and the predictors of exercise self-efficacy among patients after AMI.MethodsA cross-sectional study design was used with a conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The main finding of this study shows us the perceived benefits of PE practice with WB-EMS, among which are: enjoyment, increased physical fitness, personal accomplishment, overall body improvement and increased muscle strength, as other 215 authors have shown in their studies, with a healthy population [24,25,37,38]. In relation to personal achievements, there is another study that supports our finding, in which Shajraw and colleagues [39] state that in the greatest perceived benefits in patients with myocardial infarction, 218 were related to personal factors, such as: I like to exercise, and also my physical performance, e.g., my muscle tone improves with exercise and exercising increases my endurance. There is little evidence from specific studies with WB-EMS on perceived benefits, hence our research.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The main finding of this study shows us the perceived benefits of PE practice with WB-EMS, among which are: enjoyment, increased physical fitness, personal accomplishment, overall body improvement and increased muscle strength, as other 215 authors have shown in their studies, with a healthy population [24,25,37,38]. In relation to personal achievements, there is another study that supports our finding, in which Shajraw and colleagues [39] state that in the greatest perceived benefits in patients with myocardial infarction, 218 were related to personal factors, such as: I like to exercise, and also my physical performance, e.g., my muscle tone improves with exercise and exercising increases my endurance. There is little evidence from specific studies with WB-EMS on perceived benefits, hence our research.…”
Section: Discussionsupporting
confidence: 86%
“…Other authors, in addition to lack of time, include social influence and "lack of skills" as prevalent barriers in people with obesity [45]. Another study included as a barrier the lack of places to exercise and internal factors related to the effort itself, such as concern about fatigue during exercise participation in patients with myocardial infarction [39].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that these personal facilitators and barriers influence the nature of physical activities performed by patients with heart failure, as they impact the individual’s confidence in their ability to succeed in those activities [ 22 ]. Another study revealed that a positive relationship between physical activity situations performed and physical activity self-efficacy in middle-aged and older adults who perceive exercise benefits, coupled with a negative relationship with perceived exercise barriers[ 23 ]. Furthermore, self-care efficacy is strongly linked to patients’ capacity to perform daily activities, return to work, and self-care behaviours, and is a crucial factor in adjusting to illness [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 Common barriers to exercise adherence reported include work commitments, lack of exercise equipment, pain, injuries, age, and chronic health conditions. 18,19 Recently, the COVID-19 pandemic presented unique challenges to exercise, particularly for older adults. 20,21 As community centers and gyms closed because of COVID-19, maintaining exercise became more difficult.…”
mentioning
confidence: 99%
“…After a major cardiac event, a downward trend in exercise adherence has been observed, with 78% not adhering to exercise guidelines after discharge 17 . Common barriers to exercise adherence reported include work commitments, lack of exercise equipment, pain, injuries, age, and chronic health conditions 18,19 . Recently, the COVID-19 pandemic presented unique challenges to exercise, particularly for older adults 20,21 .…”
mentioning
confidence: 99%